Development and Validation of Sports Betting Addictive Behaviour Scale (Global Journal of Human-Social Science, 2021)
There has been growing societal problems relating to gambling particularly those related to crime Recently gambling has been tilting towards sports betting since other forms of gambling are gradually fading away Unfortunately there is no specific tool to measure addiction to sports gambling This informed the development and validation of sports betting addictive behaviour scale A total of 366 Male 325 Female 39 sports bettors were selected from three major towns in Benue state including Makurdi Gboko and Otukpo Using literature review and focused group discussion 59 items were generated Using 5 lecturers and 2 Postgraduate students content and face validity were established respectively The already standardized gambling addictive behaviour for adolescents scale was used to establish convergent validity
Keywords: sports; betting; addictive behaviour; reliability; validity